Box : Henry Brown mails himself to freedom - Weatherford, Carole Boston, 1956- (Candlewick Press, 2020)
Lyrical text in poetic stanzas with illustrations recount the life of Henry Brown, a slave who escaped to freedom by mailing himself in a freight box. Concludes with a timeline and additional information about the writing of the book.